An adaptive observer for wind velocity using a new torque model of a wind turbine. Issue 10 (2nd October 2016) - Villanueva, Juvenal; Alvarez-Icaza, Luis; Arriaga-Trejo, Israel Alejandro; Simón, Jorge; Flores, Jorge
ABSTRACT: In this paper, a new mechanical torque model of a wind system is presented, which is used to design an adaptive observer, whose goal is to estimate the wind speed and the mechanical torque in a wind turbine. This adaptive observer allows to obtain, in real time, the turbine maximum power point with wind turbine power control purposes without requiring the precise knowledge of the performance coefficient curve or look-up tables, that are currently used in most control schemes. The new model is compared with a heuristic model and validated with an experimental system.